Parent-adolescent communication about sexual and reproductive health including HIV and STIs in Oman. Issue 5 (3rd September 2022) - Al Zaabi, Omar; Heffernan, Margaret E.; Holroyd, Eleanor; Jackson, Mervyn
ABSTRACT: Parent-adolescent sexual and reproductive health (SRH) communication plays an important role in reducing sexual risk behaviour and preventing HIV. We sought to enhance limited information about the unique barriers to parent-adolescent SRH communication in the Arab states. This mixed-methods study, using a two-phase sequential explorative design, was conducted in 15 public secondary schools (with grades 5 to 10 students aged 10 to 15 years) in Oman. In phase one, 15 parents participated in two single-sex focus group discussions and two in-depth individual interviews. The qualitative data were analysed using thematic analysis. In phase two, a convenience sample of 250 parents completed a paper-based self-administered questionnaire. Findings showed that parents rarely communicated with their children about SRH concerns, including HIV. Barriers to more open parent-adolescent SRH communication include the fear that such discussion might encourage early sexual debut; feelings of shyness, discomfort and shame; associated socio-cultural taboos; gender mismatch; and lack of SRH knowledge. Findings suggest the need for parental SRH education and training and school based SRH education programmes to improve adolescent SRH. Experience developing these may be helpful to other countries with similar religious beliefs and socio-cultural traditions seeking to improve parent-adolescent SRH communication.